2004
DOI: 10.1021/bi048147g
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the Substrate Specificity of the β-Ketoacyl-Acyl Carrier Protein Synthase Domain of Module 2 of the Erythromycin Polyketide Synthase

Abstract: The beta-ketoacyl-acyl carrier protein synthase (KS) domain of the modular 6-deoxyerythronolide B synthase (DEBS) catalyzes the fundamental chain building reaction of polyketide biosynthesis. The KS-catalyzed reaction involves two discrete steps consisting of formation of an acyl-enzyme intermediate generated from the incoming acylthioester substrate and an active site cysteine residue, and the conversion of this intermediate to the beta-ketoacyl-acyl carrier protein product by a decarboxylative condensation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…This hypothesis would be consistent with the well-established mechanism for chain length control by iterative (type II) PKSs (28). Alternatively, the tetraketide may be back-transferred to KS3, but fail to undergo another round of chain elongation, also observed in prior studies on DEBS module 2 in which di-and triketide substrates could be loaded onto the KS domain but could not undergo subsequent chain elongation (29). Notably, such an abortive back-transfer would be expected to result in eventual inactivation of the KS3 domain by the deadend intermediate.…”
Section: Resultssupporting
confidence: 86%
“…This hypothesis would be consistent with the well-established mechanism for chain length control by iterative (type II) PKSs (28). Alternatively, the tetraketide may be back-transferred to KS3, but fail to undergo another round of chain elongation, also observed in prior studies on DEBS module 2 in which di-and triketide substrates could be loaded onto the KS domain but could not undergo subsequent chain elongation (29). Notably, such an abortive back-transfer would be expected to result in eventual inactivation of the KS3 domain by the deadend intermediate.…”
Section: Resultssupporting
confidence: 86%
“…Thus, acyl transfer between an ACP and the immediate downstream KS may be difficult to control, leading to relatively limited enzymatic selectivity, and a potentially reversible process. Indeed, it has been observed that a large excess of SNAC thiol is able to remove an acyl group from the KS active site by transthioesterification [22] .…”
Section: Acyl Chain Elongation Drives Ketosynthase Substrate Selectivmentioning
confidence: 99%
“…Besides the active-site Cys (36), each KS domain harbors a pair of universally conserved His residues (for example, His 334 and His 374 in DEBS KS5) that facilitate the decarboxylation and condensation reactions (37,38). (2S,3R)-2-Methyl-3-hydroxypentanoyl-N-acetylcysteamine thioester (NDK-SNAc), the N-acetylcysteamine acyl thioester analog of the natural ACP-bound syn-diketide substrate of DEBS module 2, can conveniently be used as a surrogate substrate for DEBS KS domains (39,40).…”
Section: Ks Domainsmentioning
confidence: 99%